2020
DOI: 10.5194/amt-13-4499-2020
|View full text |Cite
|
Sign up to set email alerts
|

MAX-DOAS measurements of tropospheric NO<sub>2</sub> and HCHO in Munich and the comparison to OMI and TROPOMI satellite observations

Abstract: Abstract. We present two-dimensional scanning Multi-AXis Differential Optical Absorption Spectroscopy (MAX-DOAS) observations of nitrogen dioxide (NO2) and formaldehyde (HCHO) in Munich. Vertical columns and vertical distribution profiles of aerosol extinction coefficient, NO2 and HCHO are retrieved from the 2D MAX-DOAS observations. The measured surface aerosol extinction coefficients and NO2 mixing ratios derived from the retrieved profiles are compared to in situ monitoring data, and the surface NO2 mixing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
50
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 87 publications
12
50
2
1
Order By: Relevance
“…In former publications (e.g. Irie et al, 2008;Clémer et al, 2010;Frieß et al, 2016;Bösch et al, 2018) and also during this comparison study, it was found that MAX-DOAS vertically integrated aerosol profiles systematically underestimate AOTs. It has already been pro-J.-L. Tirpitz et al: CINDI-2 profiling comparison Figure 10.…”
Section: Aerosol Optical Thicknesssupporting
confidence: 65%
See 2 more Smart Citations
“…In former publications (e.g. Irie et al, 2008;Clémer et al, 2010;Frieß et al, 2016;Bösch et al, 2018) and also during this comparison study, it was found that MAX-DOAS vertically integrated aerosol profiles systematically underestimate AOTs. It has already been pro-J.-L. Tirpitz et al: CINDI-2 profiling comparison Figure 10.…”
Section: Aerosol Optical Thicknesssupporting
confidence: 65%
“…The scaling factor is applied to the measured O 4 dSCDs prior to the retrieval and was initially motivated by previous MAX-DOAS studies which reported a significant yet debated mismatch between measured and simulated dSCDs (e.g. Wagner et al, 2009;Clémer et al, 2010;Ortega et al, 2016;Wagner et al, 2019, and references therein). Also for MAPA during CINDI-2, a scaling factor of 0.8 was found to improve the dSCD agreement, enhance the number of valid profiles and significantly improve the agreement with the Sun photometer aerosol optical thickness (Beirle et al, 2019).…”
Section: Participating Groups and Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…λ indicates the wavelength shift parameter. X r (λ) refers to the Raman spectrum (Chance and Spurr, 1997), and α r is the fitted coefficient to X r (λ). α j refers to the cross section of trace gas j .…”
Section: Radiance Fittingmentioning
confidence: 99%
“…In addition, in situ measurements are only representative for a very small area surrounding the station and governed by local emissions and meteorological conditions [5,6]. Spaceborne observations provide indispensable spatial distribution information of atmospheric pollutants like NO 2 on a global scale.…”
Section: Introductionmentioning
confidence: 99%